IoT-Based Smart Energy Meter for Real-Time Electrical Power Monitoring: A Systematic Review - Muhammad Raihan Abiyyu; Zidni Ma'ruf; Deka Rahmat Dhani; Imam Alfajri (Jurnal Pendidikan Sains dan Komputer, 2026)
The rapid advancement of the Internet of Things (IoT) has significantly transformed electrical energy monitoring by enabling real-time data acquisition, remote accessibility, and intelligent energy management. IoT-based smart energy meters integrate sensors, microcontrollers, communication technologies, and cloud platforms to monitor key electrical parameters, including voltage, current, power, and energy consumption. Despite extensive research in this field, existing studies exhibit considerable variation in hardware architectures, communication protocols, monitoring capabilities, and integration with advanced energy management systems. Therefore, this study presents a systematic review of recent developments in IoT-based smart energy meters for real-time electrical power monitoring. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Relevant articles published between 2023 and 2026 were collected from ScienceDirect, IEEE Xplore, SpringerLink, and Google Scholar, resulting in 14 eligible studies for qualitative synthesis. The findings indicate that ESP32-based platforms, voltage and current sensing technologies, Wi-Fi communication, and MQTT protocols dominate current implementations due to their cost-effectiveness and real-time monitoring capabilities. Furthermore, the review highlights emerging trends involving renewable energy integration, cloud-based analytics, machine learning applications, and smart grid interoperability. However, critical challenges remain regarding cybersecurity, scalability, interoperability, bidirectional energy monitoring, and integration with industrial control systems. This review provides a comprehensive overview of current technological developments, identifies research gaps, and proposes directions for developing intelligent, secure, and scalable IoT-based energy monitoring systems to support next-generation smart grids and sustainable energy management.